PENGARUH FRAUD PENTAGON TERHADAP KECURANGAN LAPORAN KEUANGAN (Studi Kasus Pada Perusahaan Sub Sektor Otomotif Dan Komponen Yang Terdaftar Pada Bursa Efek Indonesia Tahun 2017 – 2019) - Reswan Christian Simbolon; Valentine Siagian (Jurnal Ekonomis, 2021)
The purpose of this study aims to examine the impact of the pentagon fraud partially and simultaneously to some extent, on fraud in financial statements. In this study, secondary data from the annual reports and finances of automotive sector companies listed on the IDX are used in the 2017-2019 period. This study uses a purposive sampling method in selecting samples and then produces 36 samples from 12 automotive and component companies for the year 2017-2019. Logistic regression analysis in this study used SPSS 23 software in analyzing the data obtained. The results of this study simultaneously show that the pentagon fraud has a significant effect on financial statement fraud in automotive and component sector companies listed on the Indonesia Stock Exchange in 2017 - 2019 which means that if the fraud pentagon value changes, the financial statement fraud will also change. Partially pressure, opportunity, and arrogance have no significant effect on financial statement fraud where pressure, opportunity and arrogance do not affect the value of financial statement fraud, rationalization has a significant negative effect on financial statement fraud, which means rationalization affects the opposite, while ability has a significant positive effect on fraudulent financial statements in automotive and component sector companies listed on the Indonesia Stock Exchange for the 2017-2019 period, which means if the value of ability increases, financial statement fraud increases.